2021
DOI: 10.3389/fphar.2021.692349
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Acetaminophen and Metformin Hydrochloride in Rats After Exposure to Simulated High Altitude Hypoxia

Abstract: The pharmacokinetic characteristics of drugs were altered under high altitude hypoxia, thereby affecting the absorption, distribution, metabolism, and excretion of drug. However, there are few literatures on the pharmacokinetic changes of antipyretic and pain-relieving drugs and cardiovascular system drugs at high altitude. This study aimed to evaluate the pharmacokinetics of acetaminophen and metformin hydrochloride in rats under simulated high altitude hypoxia condition. Mechanically, the protein and mRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
(35 reference statements)
0
4
1
Order By: Relevance
“…As one of the body’s defense systems against foreign bodies, white blood cell count can reflect the immune status of the body. The results of the present study indicated an increase in the white blood cell count of rats in both the acute and chronic hypoxia groups, indicating that hypoxic conditions may induce inflammatory responses, which was inconsistent with a previous finding [ 43 ] that reported a decrease in the white blood cell count of rats in a hypoxic environment. The differences in results could be attributed to differences in study methodology, hypoxia modeling method, modeling time of rats, and the noncontinuous hypoxia state and hypoxia time caused by the need for animal treatment during the simulated hypoxia modeling period.…”
Section: Discussioncontrasting
confidence: 99%
“…As one of the body’s defense systems against foreign bodies, white blood cell count can reflect the immune status of the body. The results of the present study indicated an increase in the white blood cell count of rats in both the acute and chronic hypoxia groups, indicating that hypoxic conditions may induce inflammatory responses, which was inconsistent with a previous finding [ 43 ] that reported a decrease in the white blood cell count of rats in a hypoxic environment. The differences in results could be attributed to differences in study methodology, hypoxia modeling method, modeling time of rats, and the noncontinuous hypoxia state and hypoxia time caused by the need for animal treatment during the simulated hypoxia modeling period.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, changes in the PK of acetaminophen and metformin hydrochloride have been observed in rats under simulated high altitude hypoxic conditions. These modifications were driven by a significant decrease in the transcription of uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) and organic cation transporter 2 (OCT2) (Zhu et al, 2021). A fine control of the major liver enzymes, or the levels of circulating metabolites of drugs with a low therapeutic index, is therefore mandatory for the definition of safe and effective therapy.…”
Section: An Hypoxic Environment Can Influence Xenobiotic Metabolismmentioning
confidence: 99%
“…Simulated high-altitude hypoxic conditions revealed a decline in the transcription of organic cation transporter 2 and uridine diphosphate glucuronosyltransferase 1A1 leading to changes in the pharmacokinetics of metformin and acetaminophen. [ 44 ] Additional evidence is required about identified genes and enzymes, particularly the ones involved in metabolizing common drugs used in spaceflight. In addition, one has to focus on drug-drug and drug-diet interactions in spaceflight.…”
Section: Physiological Alterations In Space and Their Significance On...mentioning
confidence: 99%